Bioefficacy of some novel and safer pesticides against fruit borer, Helicoverpa armigera in capsicum - Sahu, Nandini; Mandal, S M A (Indian Journal of Plant Protection, 2020)
Experiments were conducted during winter season, 2016-2017 at Central Research Station, Odisha University of Agriculture and Technology, Bhubaneswar to evaluate the bio efficacy of some novel and safer pesticides against fruit borer, Helicoverpa armigera in capsicum. The highest reduction of H. armigera larval population by 93.55 and 94.59 % was recorded from cyantraniliprole 10.26 OD @ 70 ml a.i./ha followed by cyantraniliprole 10.26 OD @ 60 ml a.i. /ha (92.47 and 93.24%), emamectin benzoate 5 SG @ 10 g a.i./ha (91.40 and 91.89 %) and fipronil 5 SC @ 50 ml a.i./ha (90.32 and 90.54 %) in the first and second (4.11.16 and 22.11.16) dates of transplanting, respectively. Among the microbial pesticides, highest reduction of larval population was recorded in Bacillus thuringiensis var. kurstaki @ 1.0 L/ha (81.72 and 83.78 %) followed by Beauveria bassiana @ 2.5 L/ha (75.27 and 78.38 %).